DESIGN OF SMARTSCHOOL WEBCAM SECURITY SYSTEM USING RASPBERRY PI WITH MOTION DETECTION IN SMK PGRI SUKODADI - Yudianto, Firman; Susanto, Fajar Annas (JOURNAL ASRO; Vol 11 No 1 (2020): International Journal of ASRO, 2020)
Currently a low cost security system is needed and easy to apply especially at educational institutions that will implement smart school and industry 4.0. Needed devices are raspberry pi and web camera. Raspberry pi will only save moving images taken from the web camera. Because by storing an image whose file size is not too large will ease the performance of the server. In this study, a design for the raspberry pi based motion detection system will be applied at SMK PGRI Sukodadi Lamongan Regency which has not have security system. This system will save the file in the form of an image that will be put together into a moving image that looks like a video that will displayed in a LED monitor. Keywords: smart school, motion detection, moving image.